Performance Analysis of Pulsating Water Jet Machining During Disintegration of Rocks by Means of Acoustic Emission - Tripathi, R.; Srivastava, M.; Hloch, S.; Chattopadhyaya, S.; Das, A.; Pramanik, Alokesh; Klichová, D.; Adamcik, P. (2018)
Over the decades, water jet cutting has been widely used for rock disintegration in mining operations and quarrying purposes. The impact of high-pressure water jet on hard material like rock, coal ruins the original structure of the material; therefore, low-pressure water jet comes into the existence. In recent year, pulsating water jet has been applied in numerous ways such as surface cleaning, exclusion of damaged material layers, preparation of surfaces, and disintegration of mate rials. It has also a great potential for application in hard rock breakage as conventional methods are cumbersome, not readily accessible and have economical limitations. The performance of the jet increases significantly by the generation of pulses causing disintegration of material at a relatively lower energy and costs. This paper focuses on the study of the disintegration processes of marble and granite by pulsating water jet subjected to erosion via acoustic emission. The experiments are performed by using pulsating water jet with modulation frequency of 20.20, kHz. The MVT circular nozzle with an orifice diameter of 0.9, mm, standoff distance from the target material 6, mm, traverse speed varied from 2 to 16, mm/s, and pump pressure 60, MPa was used for water jetting. The topography of granites and marble on the cut depth and surface quality were investigated by the optical profile meter. Moreover, dependable relations between some physical and mechanical properties of the rocks and the depth of cut were observed. The online monitoring of acoustic emission shows the change in response to the pulse frequency at different time intervals.